Clinical Spectrum of Advanced Neuroblastoma - Alia Ahmad (Journal of Rawalpindi Medical College, 2017)
Background: To analyze the spectrum of neuroblastoma and burden of high risk malignancy on the public sector tertiary center. Methods: In this descriptive study, 70 patients with neuroblastoma were enrolled. Data regarding their age, sex, type (infantile <547 days or 18 months or more than 18 months), staging and clinical features, bone and bone marrow involvement, course of therapy and outcome was analyzed . The staging was done on the basis of bilateral bone marrow biopsy and imaging CT Scans, MRI neck chest and abdomen and bone scans. Patients were treated with conventional vincristine, cyclophosphamide, doxorubicin, etoposide and carboplatin for 6-8 courses 2-3 weeks apart depending upon the age whether 18 months or older group. Evaluation was done after 2-4 courses to see the response and options for surgery by doing imaging in the form of MRI or CT scans. Results: Total 70 patients with age ranging from< 1 year to 15 years (median age of 3 yrs) were included. M: F Ratio was 1.8:1. Non-infantile type (70%), stage IV (79%) and adrenal mass (47%) were the commonest presentations. Bone and bone marrow involvement was seen in 53% and 70% , respectively. Thirty out of seventy (43%) successfully completed the chemotherapy, 12/70(17%) abandoned treatment, 17/70 (24%) expired due to progressive disease and infections, 7/70(10%) were put on palliative treatment at presentation 4/70(6%) relapsed and given palliation therapy. Conclusion: In resource limited settings, neuroblastoma stage IV is a challenging malignancy to deal with. There is intense need of increased capacity building to diagnose them early and implementation of effective infection control measures with better survival options in these patients.